Genetic and experimental evidence for the involvement of the CD6 lymphocyte receptor in psoriasis. Issue 10 (October 2018) - Consuegra-Fernández, Marta; Julià, Marc; Martínez-Florensa, Mario; Aranda, Fernando; Català, Cristina; Armiger-Borràs, Noelia; Arias, María-Teresa; Santiago, Francisca; Guilabert, Antonio; Esteve, Anna; Muñoz, Carlos; Ferrándiz, Carlos; et al.
Abstract Psoriasis is a chronic inflammatory skin disease with a strong genetic background and is triggered by environmental factors. Available evidence supports CD6, a lymphocyte surface receptor mostly expressed by T cells, as a putative target in autoimmunity. Accordingly, a humanized anti-CD6 antibody has been assayed for the treatment of certain autoimmune disorders, including psoriasis. Here, we present novel evidence in mice and humans for a direct involvement of CD6 in psoriasis pathophysiology. First, an attenuated form of imiquimod-induced psoriasis-like skin inflammation was demonstrated in CD6-deficient mice, as deduced from lower epidermal thickness and local reduced production of pro-inflammatory cytokines, namely, interleukin-17A. Thus, isolated CD4+ CD62L+ T cells from CD6-deficient mice displayed decreasedin vitro T-helper type 17 polarization. Second, a statistically significant association between CD6 single-nucleotide polymorphisms (rs17824933, rs11230563 and rs12360861) and more severe forms of psoriasis was demonstrated in a cohort of 304 patients at three public hospitals from the metropolitan area of Barcelona. Taken together, these results provide new supportive evidence of the contribution of the CD6 lymphocyte receptor in psoriasis at both experimental and clinical levels.